Comparative analysis of trends in the burden of motor neuron disease in China, the United States, and globally from 1990 to 2021: projections for 2022–2041 - Peng, Bo; Tu, Yuluo; Zhou, Cheng; Xie, Gui; Xiong, Jia; Huang, Kai; Hu, Suifa (Frontiers in Neurology, 2025)
BackgroundMotor Neuron Disease (MND) is a neurodegenerative disorder with low incidence (4–8 per 100,000), but high disability and mortality. This study analyzes MND burden in China, the U.S., and Globally from 1990 to 2021, covering trends in incidence, prevalence, mortality, Disability-Adjusted Life Years (DALYs), age-standardized incidence rate (ASIR), age-standardized prevalence rate (ASPR), age-standardized mortality rate (ASMR), and age-standardized DALYs rate (ASDR), and predicts changes for 2022–2041.MethodsUsing Global Burden of Disease (GBD) data, Joinpoint regression analysis identified key turning points, and decomposition analysis quantified the contributions of aging, population growth, and epidemiological factors. The Autoregressive Integrated Moving Average (ARIMA) model forecasted future trends.ResultsFrom 1990 to 2021, the incidence, prevalence, mortality, and DALYs of MND in China, the United States, and globally showed significant increases, with the largest increase observed in mortality (China +126%, USA +118%, global +156%). The annual average percentage changes (AAPC) were as follows: ASIR (−1.10, 0.45, −0.15%), ASPR (0.26, 0.39, −0.04%), ASMR (0.57, 0.51, 0.58%), and ASDR (−0.15, 0.14, 0.25%). Joinpoint regression analysis showed that China’s ASIR declined from 1990 to 2015 and began to rise in 2015, with ASPR continuing to increase and ASMR and ASDR fluctuating. In the US, ASIR continued to rise, ASPR decreased before 1995 and then increased, with fluctuations in ASMR and ASDR. Globally, ASIR and ASPR decreased from 1990 to 1995, increased from 1995 to 2005, and then declined from 2005 onwards, with ASMR continuing to increase. Decomposition analysis indicated that aging populations aged 65 and above were the primary driving factor. Gender and age analysis revealed that males under 69 bear a higher MND burden. Predictions for 2022–2041 show that in China, male ASIR will decline, while female ASIR will rise, with ASPR, ASMR, and ASDR remaining stable; in the US, male ASIR will rise, ASPR will first increase and then decrease, with ASMR and ASDR remaining stable; globally, ASIR, ASPR, and ASMR will remain stable, while male ASDR will rise and female ASDR will remain stable.ConclusionThe burden of MND continues to increase in China, the United States, and globally, with elderly males particularly affected, while low- and middle-income countries face more severe challenges. This study provides crucial data for developing global public health strategies and medical policies, aiming to effectively reduce the burden of MND through targeted interventions.